2018
DOI: 10.1161/jaha.117.007197
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal PirB Upregulated in Cerebral Ischemia Acts as an Attractive Theranostic Target for Ischemic Stroke

Abstract: BackgroundIschemic stroke is a complex disease with multiple etiologies and clinical manifestations. Paired immunoglobulin‐like receptor B (PirB), which is originally thought to function exclusively in the immune system, is now also known to be expressed by neurons. A growing number of studies indicate that PirB can inhibit neurite outgrowth and restrict neuronal plasticity. The aim of the study is to investigate whether PirB can be an attractive theranostic target for ischemic stroke.Methods and ResultsFirst,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…We also showed a specific spatial‐temporal expression pattern of MHC I during human hippocampal development (Zhang et al ). In addition, we found that MHC I expression can be induced in neurons during several pathological conditions such as stroke, where they are believed to play an active role in the disease process (Xia et al ; Wang et al, ). Other studies have shown that MHC I is induced in neurons upon interferon gamma (IFNγ) treatment (Victório et al ; Sobue et al ).…”
mentioning
confidence: 99%
“…We also showed a specific spatial‐temporal expression pattern of MHC I during human hippocampal development (Zhang et al ). In addition, we found that MHC I expression can be induced in neurons during several pathological conditions such as stroke, where they are believed to play an active role in the disease process (Xia et al ; Wang et al, ). Other studies have shown that MHC I is induced in neurons upon interferon gamma (IFNγ) treatment (Victório et al ; Sobue et al ).…”
mentioning
confidence: 99%
“…Significantly enhanced signal intensities were observed in ischemic hemispheres of the mice's cerebral cortex that had suffered an ischemic stroke after dosing a liposome formulation intravenously into a tail vein. This study indicated sound targeting effects of the liposome formulation to the ischemic cortex (Wang et al., 2018 ). Generally, liposomes are suitable carriers of anti-inflammatory reagents and can overcome undesired pharmacokinetic behaviors and reduce adverse effects.…”
Section: Drug Delivery Strategies Targeting Ischemic Strokementioning
confidence: 74%
“…After observing the increased expression of paired immunoglobulin-like receptor B (PirB) in the ischemic hemisphere of mice 24 h post-MCAO, Wang et al (2018) constructed anti-PirB immunoliposome probe with a near-infrared fluorophore that was successfully applied to in vivo imaging for upregulated PirB region in a cerebral ischemic stroke model. These authors also used soluble PirB ectodomain, as a therapeutic reagent encapsulated in liposomes, showing a significant functional recovery in a model of ischemic stroke.…”
Section: Liposomes As Drug Nanocarriersmentioning
confidence: 99%